2(x-3)+5=3(x+4)-10

Simple and best practice solution for 2(x-3)+5=3(x+4)-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-3)+5=3(x+4)-10 equation:


Simplifying
2(x + -3) + 5 = 3(x + 4) + -10

Reorder the terms:
2(-3 + x) + 5 = 3(x + 4) + -10
(-3 * 2 + x * 2) + 5 = 3(x + 4) + -10
(-6 + 2x) + 5 = 3(x + 4) + -10

Reorder the terms:
-6 + 5 + 2x = 3(x + 4) + -10

Combine like terms: -6 + 5 = -1
-1 + 2x = 3(x + 4) + -10

Reorder the terms:
-1 + 2x = 3(4 + x) + -10
-1 + 2x = (4 * 3 + x * 3) + -10
-1 + 2x = (12 + 3x) + -10

Reorder the terms:
-1 + 2x = 12 + -10 + 3x

Combine like terms: 12 + -10 = 2
-1 + 2x = 2 + 3x

Solving
-1 + 2x = 2 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-1 + 2x + -3x = 2 + 3x + -3x

Combine like terms: 2x + -3x = -1x
-1 + -1x = 2 + 3x + -3x

Combine like terms: 3x + -3x = 0
-1 + -1x = 2 + 0
-1 + -1x = 2

Add '1' to each side of the equation.
-1 + 1 + -1x = 2 + 1

Combine like terms: -1 + 1 = 0
0 + -1x = 2 + 1
-1x = 2 + 1

Combine like terms: 2 + 1 = 3
-1x = 3

Divide each side by '-1'.
x = -3

Simplifying
x = -3

See similar equations:

| -4t+16=4 | | 14-46=3(x-1)-8 | | 4u^2+12u=0 | | 4x+9=3x+8 | | 7x^2-323=0 | | 6w-15w-19=-19 | | X+2x+5x+2= | | -7(x+4)-18=12+5 | | 6=-16x^2+30x+5 | | 6=-16x+30x+5 | | 48=-2y-4y-24 | | 3/4+15/d | | -5x-22=3x+10 | | 2(x+5)-3=9 | | b-9-66=33 | | x+3/x-5=10/x-5 | | X/9+4=-3 | | 4(x+1)-3=5 | | 12x+117=4(3x+31) | | (3x^2-4x+7)+(3x-3x^2)+(x-7)=0 | | -4(1+7k)=-144 | | 33/5=9/10p | | 10x^2-105x+135= | | r-7/5=-3 | | 14=12+3 | | 7+4x=5x | | 4w^2-w(2w-3)=x | | -9/7+t=-5/9 | | 2(6x-8)=12x-16 | | a-22/7=0 | | 32x^2-18y^2=0 | | 2x+6-(4x-4)= |

Equations solver categories